CD14++CD16+HLA‐DR+ Monocytes in Peripheral Blood are Quantitatively Correlated with the Severity of Pre‐eclampsia. (5th April 2015) - Tang, Mao‐Xing; Zhang, Yong‐Hong; Hu, Lian; Kwak‐Kim, Joanne; Liao, Ai‐Hua
<x xml:space="preserve">Abstract</x> Problem We aim to investigate the proportion and absolute counts of peripheral blood monocyte subsets in women with normal pregnancy (NP) and pre‐eclampsia (PE), and their correlation with the clinical manifestation and severity of PE. Method of study Peripheral blood was obtained from women with NP (n = 30), mild PE (MPE, n = 15) and severe PE (SPE, n = 30). The proportion and absolute counts of CD16+ monocytes and the subsets including intermediate (CD14++CD16+HLA‐DR+) and non‐classical (CD14+CD16++HLA‐DR+) monocytes were determined by flow cytometric analysis. Results Women with MPE and SPE had significantly increased absolute count of CD14++CD16+HLA‐DR+ monocyte subsets (P < 0.01 each) as compared to NP women. In addition, there were significant differences in the absolute count of CD14++CD16+HLA‐DR+ monocyte subsets between MPE and SPE groups (P < 0.05). The proportion of CD14++CD16+HLA‐DR+ monocyte subsets was significantly increased in SPE compared to MPE and NP (P < 0.01 each). The absolute count (r = 0.332, P < 0.05) and proportion (r = 0.447, P < 0.01) of CD14++CD16+HLA‐DR+ monocytes were positively correlated with the severity of PE. Multivariate logistic regression analysis further revealed that the absolute count of CD14++CD16+HLA‐DR+ monocytes was a potential marker for PE (P < 0.01). Conclusion A preferential increase in peripheral blood CD14++CD16+HLA‐DR+ monocytes is quantitatively correlated with clinical manifestation of PE.